SISTEM HUKUM KETENAGAKERJAAN INDONESIA: HAK DAN KEWAJIBAN PARA PIHAK DALAM HUBUNGAN INDUSTRIAL - Muthia Syafa Ramadhani Lubis; Sifa Maulida Bangun, Marsya Oktaviani Harahap, Zahwa Soraya, Niha Sry Asyh Gultom, Mutiara Andini, E (INTELIGENSIA MEDIA, 2026)
The aim of this study is to examine the labour law system in Indonesia and to assess the rights and responsibilities of all parties in industrial relations, including workers, employers and the government. Industrial relations constitute a system of interactions that occur during the production of goods and/or services, based on the principles of Pancasila and the 1945 Constitution of the Republic of Indonesia. Maintaining a balance between the rights and responsibilities of the parties involved is a crucial aspect of creating harmonious, fair and productive labour relations. The method used in this study is normative legal research employing a statutory approach and a conceptual approach. The legal sources utilised consist of primary sources, namely legislation; secondary sources, such as books and academic journals; and tertiary sources, such as legal dictionaries and encyclopaedias. The collection of legal sources was carried out through a literature review, followed by qualitative descriptive analysis. The results of this study indicate that the labour law system in Indonesia serves to manage relations between workers, employers and the government with the aim of creating fair industrial relations. Workers are entitled to a decent wage, occupational health and safety protection, social security, and the freedom to form trade unions, and have a duty to carry out their work in accordance with their contract and to comply with the regulations set by the company. Employers are entitled to run and develop their businesses, whilst bearing the responsibility to fulfil workers’ statutory rights and provide safe working conditions. The government acts as a regulator, facilitator and supervisor in the implementation of industrial relations. The fact that the exercise of rights and obligations by all parties has not yet been optimally implemented remains a cause of disputes in industrial relations. Therefore, compliance with regulations and increased legal awareness amongst all parties are required in order to achieve harmonious, productive and sustainable industrial relations.